Ketogenic Diet Modulates NAD+-Dependent Enzymes and Reduces DNA Damage in Hippocampus - Elamin, Marwa; Ruskin, David N.; Masino, Susan A.; Sacchetti, Paola (Frontiers in Cellular Neuroscience, 2018)
The ketogenic diet’s (KD) anti-epileptic effects have long been documented. Recently, its therapeutic potential in multiple neurodegenerative and neurodevelopmental disorders has emerged. Yet experimental evidence for a fundamental mechanism underlying beneficial effects across numerous diseases remains lacking. We previously showed that feeding rats a KD produced an early (within 2 days) and persistent elevation of hippocampal nicotinamide adenine dinucleotide+ (NAD+), an essential metabolic coenzyme and signaling molecule. NAD+ is a marker of cellular health and a substrate for enzymes implicated in longevity and DNA damage repair such as sirtuins and poly-ADP ribose polymerase-1 (PARP-1). As a result, activation of NAD+-dependent enzymes’ downstream pathways could be the origin of KD’s broad beneficial effects. Here rats were fed ad libitum regular chow or KD for two days or three weeks and the levels of hippocampal sirtuins, PARP-1, and the oxidative DNA damage marker 8-hydroxy-2`-deoxyguanosine were quantified. We found a significant immediate and persistent increase in the collective activity of nuclear sirtuin enzymes, and a significant augmentation of Sirt1 mRNA at two days. Levels of PARP-1 and 8-hydroxy-2`-deoxyguanosine decreased after two days of treatment and further declined at three weeks. Our data show that a KD can rapidly modulate energy metabolism by acting on NAD+-dependent enzymes and their downstream pathways. Thus, therapy with a KD can potentially enhance brain health and increase overall health span via NAD+-related mechanisms that render cells more resilient against DNA damage and a host of metabolic, epileptic, neurodegenerative, or neurodevelopmental insults.